Time use research and time use data - actual topics and new frontiers - Joachim Merz (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2002)
This paper is asking about the actual used and appropriate data for recent substantive time use research. Emphasis is laid on both, macroanalytic and microanalytic approaches. However, the focus is on microeconomic approaches with topics on time use in the labour market (labour supply) and household production including the shadow pricing of unpaid work. Based on a structured survey about time use research and their data, actual topics, advantages and disadvantages of the data connected with the requirements on the research frontier and hints for further needs and developments are discussed. – – Diese Studie thematisiert den Gebrauch und die geeigneten Daten für die aktuelle inhaltlich ausgerichtete Forschung zur Zeitverwendung. Betrachtet werden sowohl makro- als auch mikroanalytische Ansätze. Allerdings liegt der Schwerpunkt auf mikroökonomischen Ansätzen mit den Topics: Arbeitsmarkt (Arbeitsangebot) und Haushaltsproduktion einschließlich der Schattenpreisgestaltung unbezahlter Arbeit. Auf der Basis eines strukturierten Überblicks über die Zeitverwendungsforschung und ihren Daten, werden aktuelle Schwerpunkte, Vor- und Nachteile der Daten verbunden mit den Erfordernissen der Forschungsfront und Hinweisen für weiteren Bedarf und Entwicklungen diskutiert.
Keywords: J20; J23; 330; Time use research; time use data; time budget; macro- and micronanalytic approaches; Zeitverwendungsforschung; Zeitverwendungsdaten; Zeitbudget; makro- und mikroanalytische Ansätze; Zeitverwendung; Theorie